FACIES ARCHITECTURE AND LATE PLIOCENE – PLEISTOCENE EVOLUTION OF A FELSIC VOLCANIC ISLAND, MILOS, GREECE - Stewart A.L.; Mcphie J. (My University, 2006)
The volcanic island of Milos, Greece, comprises an Upper Pliocene –Pleistocene, thick (up to 700 m), compositionally and texturally diverse succession of calc-alkaline, volcanic, and sedimentary rocks that record a transition from a relatively shallow but dominantly below-wave-base submarine setting to a subaerial one. The volcanic activity began at 2.66±0.07 Ma and has been more or less continuous since then. Subaerial emergence probably occurred at 1.44±0.08 Ma, in response to a combination of volcanic constructional processes and fault-controlled volcano-tectonic uplift. The architecture of the dominantly felsic-intermediate volcanic succession reflects contrasts in eruption style, proximity to source, depositional environment and emplacement processes. The juxtaposition of submarine and subaerial facies indicates that for part of the volcanic history, below-wave base to above-wave base, and shoaling to subaerial depositional environments coexisted in most areas. The volcanic facies architecture comprises interfingering proximal (near vent), medial and distal facies associations related to five main volcano types: (1) submarine felsic cryptodome-pumice cone volcanoes; (2) submarine dacitic and andesitic lava domes; (3) submarine-to-subaerial scoria cones; (4) submarine-to-subaerial dacitic and andesitic lava domes and (5) subaerial lava-pumice cone volcanoes. The volcanic facies are interbedded with a sedimentary facies association comprising sandstone and/or fossiliferous mudstone mainly derived from erosion of pre-existing volcanic deposits. The main facies associations are interpreted to have conformable, disconformable, and interfingering contacts, and there are no mappable angular unconformities or disconformities within the volcanic succession.
Keywords: VOLCANIC FACIES ARCHITECTURE; SHALLOW MARINE VOLCANISM; FELSIC DOME-CRYPTODOME-PUMICE CONE VOLCANOES; SOUTHERN AEGEAN VOLCANIC ARC; SHRIMP; GEOCHRONOLOGY; Кайнозой::Четвертичная::Плейстоцен; Кайнозой::Неоген::Плиоцен; Cenozoic::Quaternary::Pleistocene; Cenozoic::Neogene::Pliocene